Pengembangan Media Pembelajaran Powerpoint Quizizz Untuk Meningkatkan Hasil Belajar Siswa Kelas III SD - Lestari, Fivi Setya; Asmarani, Ratih (IJPSE Indonesian Journal of Primary Science Education, 2024)
The world of education needs innovation and creativity that can help improve the quality of education. An effort that can be used to improve the quality of education is by improving student learning outcomes. Unsatisfactory student learning outcomes, especially PPKn material, are a problem that needs to be resolved. To improve student learning outcomes, an educator can use interesting learning media. The aim of this research is to improve student learning outcomes in Civics learning material on accepting rights and obligations through the development of PowerPoint Quizizz media. This research uses the ADDIE R&D research method and development model, namely Analysis, Design, Development, Implementation, Evaluation. The assessment of the suitability of the PowerPoint Quizizz media was carried out by media and media validators, as well as students and educators with three trials, namely small scale, group and large scale, and the effectiveness of the PowerPoint Quizizz media was carried out by third grade elementary school students by carrying out pre-tests and post-tests. . The research results show that the development process is in accordance with the steps in the ADDIE model. Feasibility results were obtained from the validator assessment of 84.7% with valid qualifications, and small scale trials 91.4% with very feasible qualifications, group 86% with very feasible qualifications, and large scale 99.1% with very feasible qualifications, as well as the results The effectiveness obtained from the pre-test assessment was 77% with effective qualifications and post-test 88.5% with very effective qualifications. It can be concluded based on media development trials that Powerpoint Quizizz shows significant results. To improve the learning outcomes of third grade elementary school students, the PowerPoint Quizizz learning media is very suitable and very effective to use. Pengembangan Media Pembelajaran Powerpoint Quizizz Untuk